Fabrication of LaF3 Nanochains via A Reverse Microemulsion-Solvothermal Route - Guan, Hangmin; Han, Chenliang; Zhu, Dechun (Asian Journal of Chemistry, 2013)
A novel LaF3 nanochain has been successfully prepared by the self-assembly of LaF3 nanoparticles via a reverse microemulsion-solvethermal method. The products were characterized by XRD, TEM and HRTEM. A possible formation mechanism of nanochain was proposed.